An Assessment of the Efficacy of Erbium Glass Laser Therapy in Acne Scar Treatment Using Image Analysis and Processing Methods - Wiktoria Odrzywołek; Anna Deda; Dagmara Kuca; Anna Banyś; Krzysztof Makarski; Robert Koprowski; Sławomir Wilczyński (Applied Sciences)
Background: Acne scars significantly impact skin texture and esthetics, necessitating effective treatment modalities. This study evaluates the efficacy of erbium glass laser therapy in improving atrophic acne scars using advanced image analysis techniques. Materials and methods: Twenty patients with mild to moderate atrophic scars underwent two sessions of 1550 nm erbium glass laser treatment. The clinical photographs were analyzed using a Gray-Level Co-occurrence Matrix (GLCM) to assess changes in contrast and homogeneity across the grayscale and RGB channels. The analysis revealed statistically significant improvements post-therapy, including reduced contrast and increased homogeneity, indicating a smoother and more uniform skin texture. The blue and green channels demonstrated the greatest sensitivity to surface-level textural changes, while the red channel exhibited the smallest differences, reflecting its deeper penetration and reduced sensitivity to surface alterations. Conclusions: These findings underscore the value of quantitative imaging techniques in dermatology for objectively evaluating therapeutic outcomes and optimizing treatment strategies. Erbium glass laser therapy emerges as a non-invasive and effective solution for acne scar management.